The Behavior of Aggressive Inmates: A Case Study of Robbery Offenders in Surabaya: Gambaran Perilaku Agresif Pada Narapidana Pelaku Perampokan di Surabaya - Deby Indah Aristasari; Taufik Akbar Rizqi Yunanto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Crime that has been occurring frequently lately in society is the criminal act of theft, which is highly disturbing. Violent theft is commonly known as robbery. It differs from regular theft in that it involves intentionally causing physical harm. Behavior that deliberately harms others can be termed as aggressive behavior. Aggressive behavior involves intentionally causing physical or psychological harm to someone, with potentially detrimental effects. This research aims to understand the description of aggressive behavior among robbery perpetrators in Surabaya. The researcher utilized Interpretative Phenomenological Analysis (IPA) and validated the data through triangulation, data validation, member check, and rechecking of themes. The methods employed included observation, interviews, and documentation, with thematic analysis used as the data analysis technique. During the interviews, the researcher identified three major themes: understanding specific terms, experiences behind bars, and comprehending from a comparative perspective. Additionally, a unique theme emerged related to the concept of power. The findings of this research reveal a depiction of aggressive behavior among robbery perpetrators.